Combining teaching "about" and "through" entrepreneurship: A practice to develop students' entrepreneurial competencies. Issue 4 (August 2021) - Chaker, Hajer; Jarraya, Houyem
Many universities have incorporated entrepreneurship education into their programs. However, research and the practice show that this curriculum is taught in various ways, which the authors group into three themes: teaching about entrepreneurship, teaching for entrepreneurship, and teaching through entrepreneurship. Entrepreneurship educators face several challenges, especially the difficulties in defining the best way to teach entrepreneurship and the lack of evaluation of the chosen method's effectiveness. This article focuses specifically on how entrepreneurship is taught at the Faculty of Economics and Management of Tunis and what effect it may have on the development of students' entrepreneurial competencies. It attempts to support entrepreneurship educators by describing a pilot experience consisting of combining teaching about and through entrepreneurship and a conventional method that adopts just teaching about entrepreneurship. These descriptions may help to explore and uncover what happens in the classroom and aid teachers in choosing the appropriate practices to achieve their educational objectives. The article evaluates the two programs by comparing their effects on the development of students' entrepreneurial competencies. The authors use a two-sample independent t-test to make the comparison, and the results indicate that the combined method is stronger overall than the conventional method.